The Effect of Concentration of Lithium Salt on the Structural and Transport Properties of Ionic Liquid-Based Electrolytes - Tong, Jiahuan; Wu, Shengli; von Solms, Nicolas; Liang, Xiaodong; Huo, Feng; Zhou, Qing; He, Hongyan; Zhang, Suojiang (Frontiers in Chemistry, 2020)
Ionic liquids (ILs) are used as electrolytes in high-performance lithium-ion batteries, which can effectively improve battery safety and energy storage capacity. All atom molecular dynamics simulation and experiment were combined to investigate the effect of the concentration of lithium salt on the performance of electrolytes of four IL solvents ([Cnmim][TFSI] and [Cnmim][FSI], n = 2, 4). The IL electrolytes exhibit higher density and viscosity; meanwhile, larger lithium ion transfer numbers as the concentration of LiTFSI increases. Furthermore, in order to explore the effect of the concentration of lithium salt on the ionic associations of Li+ and anion of IL, the microstructures of the lithium salt in various IL electrolytes at different concentrations were investigated. The structural analysis indicated that strong bidentate and monodentate coordination was found between Li+ and anion of all IL electrolytes. Both cis and trans isomerism of [FSI]− were observed in [FSI]−-type IL electrolyte systems. Furthermore, the existence of the ion cluster [Li[anion]x](x−1)− in IL electrolytes and the cluster became more closed and compact as the concentration of LiTFSI increases.